Application of positron emission tomography (PET/CT) in diagnosis of breast cancer. Part I. Diagnosis of breast cancer prior to treatment - Jodłowska, Elżbieta; Czepczyński, Rafał; Wyszomirska, Anna; Jarząbek, Grażyna; Kędzia, Witold; Ruchała, Marek (Contemporary Oncology/Współczesna Onkologia, 2016)
Positron emission tomography with computed tomography (PET/CT) is gaining popularity as a method for overall staging assessment of breast cancer. Currently, it is not a part of the routine workup before the beginning of treatment, because of insufficient sensitivity for the detection of small tumors (due to its limited spatial resolution), the heterogeneity of radiotracer uptake by the primary tumor, and unsatisfactory sensitivity in detection of lymph node metastases (particularly when they are small). Nevertheless, it should be considered when there is a high risk of metastases, because then initial PET/CT examination allows for accurate staging and may change the treatment algorithm in up to almost 50% of stage III patients, due to detection of distant and lymph node metastases throughout the whole body. Despite the discussed limitations of PET/CT, there is ongoing research concerning the recommendations for the examination prior to treatment. For a particular group of patients with high risk of metastases, PET/CT may be expected to become a part of the routine workup as the most appropriate staging method.